HUBUNGAN ANTARA KONFORMITAS DAN PERILAKU KONSUMTIF PEMBELIAN MERCHANDISE K-POP PADA REMAJA - Pamungkas Putra Santosa; Doddy Hendro Wibowo (Journal of Innovation Research and Knowledge, 2024)
The global development of K-pop as a cultural phenomenon, particularly among young people, understanding the factors influencing purchasing decisions in teenagers is considered important. This research aims to determine the relationship between conformity and consumptive behavior in adolescents in the context of purchasing K-pop merchandise. Researchers used volunteer sampling techniques with a sample size of 408 K-pop fans teenagers. There are two scales used in this study, namely the conformity scale and the consumptive behavior scale. The data analysis method used Pearson's product-moment correlation. The results showed a correlation of r = 0.623 with p = 0.000 (p <0.01), which means there is a significant positive relationship between conformity and consumptive behavior. This means that the higher the conformity, the higher the consumptive behavior. Conversely, the lower the conformity, the lower the consumptive behavior